Changes in the Dry Matter and Sugar Content of Nantes Type Carrots during Storage - Némethy, H.; Fehér, M. (International Journal of Horticultural Science, 2002)
Changes in the dry matter and sugar content occurring during the winter storage of Nantes type carrot hybrids grown on soils of different quality were studied in 199912000 and 200012001. The dry matter content of the varieties tested depended on the production site and on the weather conditions prevailing in the growing season. The increase in the dry matter content during winter storage reached 6 to 7 per cent in the crop grown in a dry year and 1.5 to 2 per cent in a rainy year. The sugar content was lower in the rainy year (1999) and on brown sand (Szatymaz) than in the rather dry year (2000) and on chernozem soil with residual forest (Tordas), respectively. The increase in sugar content (1 to 5 per cent) measured at the end of storage was related to the season’s weather conditions.